2019
DOI: 10.1186/s12881-019-0777-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel Usher syndrome pathogenic variants identified in cases with hearing and vision loss

Abstract: Background Usher syndrome, the most common form of inherited deaf-blindness, is unlike many other forms of syndromic hereditary hearing loss in that the extra aural clinical manifestations are also detrimental to communication. Usher syndrome patients with early onset deafness also experience vision loss due to progressive retinitis pigmentosa that can lead to legal blindness in their third or fourth decade. Methods Using a multi-omic approach, we identified three novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
1
9
0
2
Order By: Relevance
“…In a previously published analysis of translational read-through of fibroblasts that were derived from a patient suffering for Niemann-Pick A/B, the SIFT prediction was also in agreement with the biochemical results obtained, whereas the Polyphen-2 gave the opposite results [50]. Although, in silico prediction programs are frequently used, they may be erroneous in determining the specific effect of a likely pathogenic variant, yet [51]. Therefore, they should be interpreted with caution and should not be taken as a definitive approach [50].…”
Section: Discussionsupporting
confidence: 71%
“…In a previously published analysis of translational read-through of fibroblasts that were derived from a patient suffering for Niemann-Pick A/B, the SIFT prediction was also in agreement with the biochemical results obtained, whereas the Polyphen-2 gave the opposite results [50]. Although, in silico prediction programs are frequently used, they may be erroneous in determining the specific effect of a likely pathogenic variant, yet [51]. Therefore, they should be interpreted with caution and should not be taken as a definitive approach [50].…”
Section: Discussionsupporting
confidence: 71%
“…The p.(Cys759Phe) mutation—pathologic variant in the Spanish population—displays consistent genotype-phenotype correlations in for both nonsyndromic RP and USH2A. These patients display different age at diagnosis of RP and of hypoacusis depending on whether they are homozygous for this variant, compound heterozygous for this variant and a missense variant, or compound heterozygous for this variant with an additional truncating variant; legal blindness and hearing loss occurs earlier in heterozygous patients than in homozygous patients (49 vs 62 years for blindness and 53 vs 70 years for hearing loss, respectively) (Pérez-Carro et al 2018). Studies of two newly identified USH2A variants in two Korean families have demonstrated more profound and progressive hearing loss than expected for USH2, requiring cochlear implantation (Lee et al 2019).…”
Section: Usher Syndrome Type IImentioning
confidence: 99%
“…Thus, USH2A mutations with usher syndrome type IIA and an association of genotype/phenotype have been successfully linked in the patient of the studied family. Pater et al (46) recently reassigned the diagnosis of usher syndrome by identifying novel USH2A splicing variants. To the best of our knowledge, the USH2A variants c.T449G (p.L150*), c.T10695A (p.Y3565*) are novel, thereby extending the spectrum of known mutations associated with this disease.…”
Section: Discussionmentioning
confidence: 99%